Church transfusion : changing your church organically-- from the inside out - Cole, Neil, 1960-; Helfer, Phil, 1958- (Hoboken, NJ : Jossey-Bass, 2012)
"Challenges churches to transfuse themselves with the life-giving qualities and energy of the organic church movementIn Church Transfusion Neil Cole (the foremost expert on organic church) teams up with his co-founder of Church Multiplication Associates , Phil Helfer, to revisit the themes from Cole's previous books. They show conventional church leaders how to use organic principles to heal their DNA and transfuse themselves with an entirely new energy, vision, and a more missional approach to what they are and what they do.Since established churches can't start from scratch the way new ones can, nor can they shift completely the way Cole's Church 3.0 proposed, Church Transfusion not only applies the organic principles for them but also gives tangible examples of how they do indeed work to bring change from the inside out. Offers a blueprint for applying organic principles to established churches to infuse them with renewed energy and vision Neil Cole is the author of Church 3.0 and Organic Church A new title in the Leadership Network series Church Transfusion is Neil Cole's most powerful follow up to Organic Church"--
Includes bibliographical references (p. 199-203) and index.
Keywords: Church renewal; Church; RELIGION / Christian Ministry / Adult